The Potential and Mechanism of Probiotic as an Immunomodulator In Improving the Immune System to Support Body Health: A Review - Supadil, Doni; Melia, Sri; Juliyarsi, Indri; Sukma, Ade (Andalasian Livestock, 2024)
Functional food is growing along with the increasing public awareness of body health. One of them is a probiotic functional food. Probiotics according to WHO/FHO (2001) are microorganisms added to products that will benefit the health of the body if consumed sufficiently, namely 106-108 CFU/ml. Probiotics have benefits in the digestive tract, on the other hand, probiotics need nutrients for their development, namely prebiotics which are expected to change the intestinal microflora and maintain balance in the gut. Probiotics have many benefits for the health of the body, one of which is to improve the immune system. Probiotics will interact with intestinal epithelial cells and be recognized by dendrites then produce IL-12 (Interleukin-12) and IFNγ (Inferon γ) by IDC (Interstitial Dendritic Cell) which can modulate the immune response system. The secretion of IFNγ (Inferon γ) by IDC proinflammatory cytokines has a dual function where IFNγ (Inferon γ) and IL-12 (Interleukin-12) circulate in the bloodstream to reach the epithelium and help alveolar macrophages and NK (Natural Killer) cells kill VR. Then pro-inflammatory cytokines IFNγ (Inferon γ) and IL-12 (Interleukin-12) secreted in the gut ecosystem after colonizing some probiotic strains help the immune system for specific Th1/Th17 (T helper cell) immune response. in addition, dendrite 4 cells will secrete IL-17 (Interleukin-17) which enhances the innate immune response. Probiotics can help B lymphocytes differentiate into plasma cells that can secrete specific immunoglobulin A. Some bacteria that can improve the immune system are Lactobacillus casei L431, Lactobacillus rhamnosus GG, Bifidobacterium longum Subsp Infantis R0033, Pediococcus acidilactici DS1, Lactobacillus plantarum HD02 and many more. In the future, probiotics can be developed as immunotherapy and other diseases such as cancer to improve the quality of human life.